Transformasi Operasional KL Lazismu Tingkat Wilayah Jawa Barat melalui Pelatihan Lean Management untuk Distribusi Bantuan yang Lebih Cepat dan Tepat - Nurul Aziz Pratiwi; Minhajuddin Minhajuddin; Kenny Nabila Putri; Muhammad Wildan Sidiq (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
West Java Province has 3.88 million people living in poverty (7.89%), placing significant demands on social institutions such as Lazismu to distribute aid swiftly, accurately, and accountably. However, Lazismu's regional Service Offices (KL) continue to face operational challenges including distribution delays, duplicate beneficiary data, weak inter-unit coordination, and limited human resource capacity. This community service activity aimed to strengthen the capacity of KL Lazismu personnel through lean management training to achieve more efficient and targeted aid distribution. The methodology encompassed field observation, value stream mapping, interactive training through a problem-based learning approach, and evaluation via pre-test and post-test instruments. The training involved 16 Lazismu scholarship recipients from Universitas 'Aisyiyah Bandung. Evaluation results revealed an average comprehension improvement of 28.7%, surpassing the minimum target of 20%. The highest gains were recorded in amil primary duties (40%), followed by lean management (36%), and communication competency (36%). Two aspects reached perfect scores of 100%: the principles of trust and transparency, and amil communication competency. These findings demonstrate that lean management training is effective in building the competency of zakat institution personnel while establishing a strong foundation for the operational transformation of aid distribution toward greater efficiency, transparency, and measurable social impact.